On finite-time output feedback sliding mode control of an elastic multi-motor system - Pham Tuan Thanh; Tran Xuan Tinh; Dao Phuong Nam; Dao Sy Luat; Nguyen Hong Quang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In this paper, the tracking control scheme is presented using the framework of finite-time sliding mode control (SMC) law and high-gain observer for disturbed/uncertain multi-motor driving systems under the consideration multi-output systems. The convergence time of sliding mode control is estimated in connection with linear matrix inequalities (LMIs). The input state stability (ISS) of proposed controller was analyzed by Lyapunov stability theory. Finally, the extensive simulation results are given to validate the advantages of proposed control design.